Interdisciplinary-Based Islamic Religious Education (PAI) Learning in Elementary Schools - Muh. Syamsuddin; Sufraini; Sedya Santosa; Tegar Setia Budi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
Islamic Religious Education (PAI) is a weekly mandatory subject often taught through lectures, resulting in passive student engagement and a lack of creativity. This study explores an innovative interdisciplinary approach to PAI at Bustanul Ulum Islamic Elementary School, integrating it with subjects like natural and social sciences, civics, Indonesian language, and mathematics. The research employs a descriptive qualitative methodology, using interviews, observations, and documentation. Data analysis involves data reduction, presentation, and conclusion drawing. Findings show that the interdisciplinary approach makes PAI more engaging and meaningful, reducing student boredom. Effective implementation requires competent teachers and collaboration among subject teachers for integration